Franchising globally : innovation, learning and imitation - Alon, Ilan (New York, NY : Palgrave MacMillan, 2010)
'Franchising Globally is first of its kind to examine franchising both from an entrepreneurial and from an international perspective. The book includes theoretical discussions and practical examples of international franchising as well as both micro and macro studies of franchising environments in different parts of the world'--Provided by publisher.
PART I: FRANCHISING APPROACHES AND FRAMEWORKS -- Franchising In Emerging Markets / I. Alon, D. Welsh & C. Falbe -- Franchising as an Entrepreneurial Form / I. Alon M. Sardy -- Internationalization of Franchising / I. Alon, L. Ni & R. Wang -- Clustering For International Market Selection / I. Alon & A. Shoham -- PART II: AREA STUDIES OF FRANCHISING -- Franchising in Italy / I. Alon & D. .Vianneli -- Franchising in Morocco / I. Alon & R. Alami -- Franchising in Croatia / I. Alon, M. Alpeza & A. Erceg -- Microfranchising in Less Developed Countries / I. Alon, M. Munoz & M.C. Mitchel -- PART III: INTERNATIONAL FRANCHISING CASES -- Ruth's Chris Franchises Expand Internationally / I. Alon & A. Kupetz -- International Franchising at Best Western / I. Alon, G. Cliquet, M.C. Mitchel & R.Perrigot -- San Francisco Coffee House Opens in Croatia / I. Alon, M. Alpeza & A. Erceg -- Athlete's Foot Master Franchisee in China / I. Alon -- Final Reflections.
Includes bibliographical references and index.
Keywords: Franchises (Retail trade); International trade